SPIRITUAL VALUES OF CUSTOMARY LAW - Kuswardani kuswardani; Marisa Kurnianingsih; Andria Luhur Prakoso (Jurnal Jurisprudence, 2018)
Recognition of living law in society or customary law / unwriten law, marking a pluralistic spiritual life that have law. Lawmakers (legislative or judge) must accommodate those values in their legal products. Moreover, judges as formers of practical law are obliged to explore and understand the values that live in society, which is the soul of the nation's personality (volkgeist), which is reflected through its Verdicts, so that the verdict can have transcendental values / spiritual values. The enactment of customary law as the basis of the Verdict of the judge or in other words the formation of the law by the judge through the Verdicts based on customary law, has existed before the Indonesian constitution is amended, namely in Article 5 paragraph (3) sub b Act No. 1/1951 About Measures - Temporary Measures for Conducting the Union of Suspended Power and Events of the Civil Courts.